THE IMPORTANCE OF RATIONALITY AND LOGIC IN RELIGIOUS PRACTICE: A STUDY OF ABD SAMAD PALIMBANI'S THOUGHT - Humaidi Humaidi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
This article elucidates the thoughts of ʿAbd al-Ṣamad al-Palimbānī (1116 H / 1704 M-1203 H / 1789 AD) regarding the role of reason and the importance of rationality in religion and society. This article refers to ʿAbd al-Ṣamad’s works as primary data and the writings of Muslim scholars as secondary data. After describing ʿAbd al-Ṣamad’s main views on reason, knowledge, and thinking, this article concludes that religious life based on rational thinking, contemplation, and critical logic will give rise to knowledge, wisdom, and moderation, support the development of human potential, and develop civilization. Conversely, a religion that is dominated by hatred and avoids critical rational thinking will give birth to ignorance, religious extremism and terrorism, and other destructive actions. This study is qualitative literature using the hermeneutic method and philosophical analysis.